Preparation method, product and application of inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane

Through the self-supported composite electrolyte membrane preparation method enhanced by inorganic electrolyte 3D fiber framework, the problem of insufficient mechanical strength and ion conductivity of solid electrolyte membranes in lithium-ion batteries is solved, and more efficient lithium ion transmission and mechanical performance improvement is achieved. It is suitable for all Solid-state energy storage devices.

CN119230932APending Publication Date: 2024-12-31HUAZHONG UNIV OF SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411371203.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The solid electrolyte membranes of existing lithium-ion batteries have shortcomings in terms of mechanical strength and ionic conductivity, and the preparation process of traditional composite electrolyte membranes is complex and costly, making it difficult to meet battery safety and performance requirements.

Method used

The self-supported composite electrolyte membrane preparation method is adopted to enhance the inorganic electrolyte 3D fiber framework. The inorganic electrolyte powder is assisted by plasticizer to form a long fiber framework, and the polymer electrolyte precursor solution is filled thereon, and the electrospinning process or wet method is used. The spinning process prepares a uniformly distributed inorganic electrolyte 3D fiber framework to improve the mechanical strength and ionic conductivity of the electrolyte membrane.

Benefits of technology

It significantly improves the mechanical strength and ionic conductivity of the composite electrolyte membrane, overcomes the problems of agglomeration and uneven distribution of inorganic electrolyte particles, and achieves more efficient lithium ion transmission paths and mechanical performance improvements, and is suitable for all-solid-state energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230932A_ABST
    Figure CN119230932A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solid-state battery materials, and discloses a preparation method of an inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane, which comprises the following steps: S1, prefabricating inorganic electrolyte powder into fibers under the assistance of a molding agent, and mutually staggering and overlapping the fibers to form an inorganic electrolyte 3D fiber skeleton; s2, dissolving a lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution, and S3, filling the inorganic electrolyte 3D fiber skeleton with the polymer electrolyte precursor solution, and heating to remove the organic solvent to obtain the inorganic electrolyte 3D fiber skeleton self-supported composite electrolyte membrane, and the step S1 and the step S2 are not in sequence. The method provided by the invention can overcome the problems of low inorganic phase content, easy agglomeration and difficult dispersion when the existing organic-inorganic composite electrolyte membrane is prepared, and the problems of insufficient ionic conductivity and poor mechanical properties of the composite electrolyte membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid-state battery materials, and more specifically, relates to a preparation method, product and application of a self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton. Background Art

[0002] At present, the application of lithium-ion batteries in various portable storage devices and large-scale grid energy storage systems has been continuously developed. However, the traditional commercially available lithium-ion batteries use an organic electrolyte plus a diaphragm configuration. When the battery is hit or the package is not tight, it is easy to cause the electrolyte to leak, causing the battery to thermal runaway. Therefore, the most effective method is to use non-flammable solid electrolytes instead of liquid electrolytes, which can greatly improve the safety of the battery.

[0003] Solid electrolytes are mainly divided into two categories: inorganic electrolytes and polymer solid electrolytes. Inorganic electrolytes have problems such as poor contact with electrode materials, complex processing technology, and high cost. Polymer solid electrolytes have advantages such as good contact with electrodes, easy processing into different shapes, and low cost. However, the ionic conductivity of polymer electrolytes is low, and it is difficult to achieve the desired effect by simply using this electrolyte. In addition, the mechanical strength of polymer electrolytes is poor, it is difficult to resist the growth of lithium dendrites, and short circuit failure is prone to occur.

[0004] Organic-inorganic composite electrolytes take into account the advantages of both inorganic electrolytes and organic polymer electrolytes. Introducing inorganic fillers into the polymer matrix can improve the ionic conductivity and mechanical properties of the polymer. However, this simple composite method is difficult to significantly improve the overall performance of the electrolyte. As the content of inorganic fillers increases, particles tend to aggregate. In addition, the mechanical strength of the composite membrane is difficult to significantly improve by relying solely on dispersed fillers, and the added content of inorganic electrolytes cannot be too high, otherwise the entire composite electrolyte membrane will be more brittle.

[0005] The patent application with publication number CN 117855596 A discloses an organic-inorganic composite solid electrolyte membrane, a preparation method thereof and a solid-state battery, including a polymer and an inorganic electrolyte, wherein the inorganic electrolyte has an internal three-dimensional interconnected porous structure and is a continuous phase, and the polymer is filled in the voids of the porous structure. In this invention, a unique structure in which the inorganic phase forms a three-dimensional interconnected skeleton and the organic phase fills the pores is obtained by "filling the inorganic substance into the organic porous membrane and hot pressing". The preparation process of the composite solid electrolyte membrane of this invention can be widely applied to a variety of combinations of polymers and inorganic materials. However, in this method, the organic electrolyte is used as the skeleton, and the inorganic electrolyte is filled into the voids by ultrasonic vibration. The inorganic particles are simply adsorbed on the surface of the organic fiber, and the poor contact between the powders causes the mechanical strength of the electrolyte membrane to be low; and the excessively high inorganic electrolyte powder content causes the flexibility of the electrolyte membrane to be poor. In addition, this method also requires hot pressing to finally prepare the electrolyte membrane. The hot pressing operation brings difficulties to large-scale industrial preparation, and at the same time increases energy consumption and costs.

[0006] Therefore, it is necessary to develop a new type of composite solid electrolyte to further improve the comprehensive performance of the electrolyte. Summary of the invention

[0007] In view of the defects of the prior art, the purpose of the present invention is to provide a preparation method, product and application of a self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton, aiming to provide a new composite solid electrolyte film with excellent mechanical strength and good conductive properties through structural design of the material at the microscopic level.

[0008] To achieve the above object, the present invention provides a method for preparing a self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton, which comprises the following steps:

[0009] S1: preforming the inorganic electrolyte powder into long fibers with the aid of a plasticizer, wherein the aspect ratio of the fibers is ≥100, preferably ≥150, and the fibers are interlaced and overlapped to form an inorganic electrolyte 3D fiber skeleton.

[0010] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution.

[0011] S3: Filling the polymer electrolyte precursor solution into the inorganic electrolyte 3D fiber skeleton, heating to remove the organic solvent, and obtaining the inorganic electrolyte 3D fiber skeleton self-supporting composite electrolyte membrane,

[0012] There is no particular order for steps S1 and S2.

[0013] In the above invention concept, the inorganic electrolyte powder is made into long fibers with the help of a plasticizer, which specifically refers to a plasticizer that is similar to a layer of skin clothing and is generally coated on the surface of the inorganic electrolyte and continuously grows to form a fiber with a relatively large length-diameter ratio. The overall shape is similar to a long string of beads, the inorganic electrolyte is similar to a "bead", and the plasticizer is similar to a "line". The beads are spaced apart or closely connected to each other, and the plasticizer is coated on the surface of the "bead", and in places where there are no beads, the plasticizer itself forms a "line". The fibers similar to the long string of beads overlap each other to form a mesh skeleton, and the inorganic electrolyte particles are equivalent to being fixed in the mesh skeleton by the capsule formed by the plasticizer, and cannot agglomerate, which fundamentally solves the problem of easy agglomeration of inorganic electrolyte particles in inorganic-organic composite electrolytes in the prior art. In addition, with the help of this method, the content of inorganic electrolyte powder in the skeleton can be further increased, and the particles can be in close contact, so that a fast lithium ion transmission channel can be formed, while improving the mechanical properties of the skeleton and the electrolyte membrane.

[0014] Furthermore, step S1 specifically comprises: dissolving an inorganic electrolyte and a plasticizer in a solvent to prepare a spinning solution, and using an electrostatic spinning process or a wet spinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton.

[0015] In the above invention concept, an inorganic electrolyte 3D fiber skeleton is prepared by an electrostatic spinning process or a wet spinning process, and the inorganic electrolyte particles are dispersed in the spinning solution, which is not easy to agglomerate, and the content of the inorganic electrolyte particles in the entire inorganic electrolyte 3D fiber skeleton can be controlled by controlling the concentration of the inorganic electrolyte particles in the spinning solution. The content can be flexibly regulated, and even the mass percentage of the inorganic electrolyte particles in the inorganic electrolyte 3D fiber skeleton can be controlled to be as high as 80%. In the traditional method for preparing inorganic-organic composite electrolytes, the mass percentage of inorganic electrolytes is generally less than 10%. The electrostatic spinning process can also make the inorganic electrolyte more evenly dispersed, thereby further increasing the content of the inorganic electrolyte in the entire composite membrane.

[0016] Furthermore, the inorganic electrolyte is an oxide solid electrolyte, including Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 0.33 La 0.557 TiO3、Li7La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Al 0.3Ti 1.7 (PO4)3、Li 3.5 Si 0.5 P 0.5 O4 is any one or a combination of at least two, the plasticizer is any one or a combination of at least two of ethylene oxide (PEO), PEO-based polymer, polyvinylidene fluoride (PVDF), PVDF-based polymer, polyacrylonitrile (PAN), PAN-based polymer, polyethylene (PE) and polypropylene (PP), and the solvent is volatile and can dissolve the plasticizer.

[0017] In the above invention concept, the solvent needs to be volatile, and it is feasible to use acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone, 1,3-dioxolane, etc. as the solvent; in addition, the plasticizer has good film-forming properties.

[0018] PEO-based polymer refers to polyethylene oxide (PEO)-based polymer electrolyte, which is a key material for solid-state sodium-ion batteries. PEO-based polymer electrolytes are considered to be promising solid electrolyte materials due to their high safety, low cost, high energy density and good electrochemical stability. PVDF-based polymer refers to polymers based on polyvinylidene fluoride (PVDF). PVDF is a polymer formed by the polymerization of vinylidene fluoride monomers, which is colorless, odorless, non-toxic, and has the characteristics of high crystallinity and low melting point. PVDF-based polymers also include PVDF-based solid electrolytes (SSE), which show great application potential in the development of solid-state lithium batteries. PAN-based polymers refer to polymers based on polyacrylonitrile (PAN). This polymer has the characteristics of good stability, strong heat resistance and good flame retardancy, and is therefore suitable for use as a matrix material. After plasticization with an organic electrolyte, a gel electrolyte can be formed.

[0019] Furthermore, the thickness of the inorganic electrolyte 3D fiber skeleton is 5μm to 100μm, and the viscosity of the spinning solution is configured to be 2 to 10Pas. The diameter and aspect ratio of the fiber can be controlled by controlling the ratio of the inorganic electrolyte, plasticizer and solvent in the spinning solution. The inorganic electrolyte is granular, and its particle size is D90≤2μm, and the preferred particle size is ≤200nm.

[0020] In the above invention concept, the thickness of the inorganic electrolyte 3D fiber skeleton is limited to 5μm~100μm, because a 3D fiber skeleton that is too thin is difficult to be self-supporting, and a too thick 3D fiber skeleton will result in a thicker final electrolyte membrane, which will bring a larger battery internal resistance and affect battery performance. The viscosity of the spinning solution is 2~10Pa s, has good fluidity, and is easy to spin. The inorganic electrolyte is granular, and its particle size is D90≤2μm (meaning that 90% of the particle size of the inorganic electrolyte powder particles is less than 2μm), and the preferred particle size is ≤200nm. Such a particle size is easier to enter the interior of the spinning fiber, and the particles are more closely connected.

[0021] Furthermore, the lithium salt is one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB, and LiDFOB, and the organic polymer molecule is any one of polyethylene oxide (PEO), PEO-based polymer, polyvinylidene fluoride (PVDF), PVDF-based polymer, polyacrylonitrile (PAN), and PAN-based polymer, or a combination of at least two thereof.

[0022] In the above inventive concept, the organic polymer molecules can be made of the same material as the plasticizer. When the two materials are the same, the inorganic electrolyte 3D fiber skeleton and the polymer electrolyte precursor solution have good wettability.

[0023] Furthermore, in step S2, the viscosity of the polymer electrolyte precursor solution prepared by lithium salt, organic polymer molecules and organic solvent is 3 to 12 Pa s. The organic solvent is one or a combination of at least two of acetonitrile, N,N-dimethylformamide, N-methylpyrrolidone and 1,3-dioxolane; the viscosity and fluidity of the solution can be regulated by controlling the mass ratio of lithium salt, organic polymer molecules and organic solvent. The precursor solution has good viscosity and fluidity, which is convenient for entering the interior of the skeleton.

[0024] Furthermore, in step S3, the polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by scraping, soaking, spin coating or micro-negative pressure adsorption, and the organic solvent is removed by heating. The polymer electrolyte precursor solution entering the inorganic electrolyte 3D fiber skeleton can provide more ion transmission paths, which is conducive to the improvement of ion conductivity. In addition, the organic polymer molecules filled inside are relatively soft, and the electrolyte membrane has good flexibility.

[0025] According to the second aspect of the present invention, there is also provided a self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton prepared by any of the above methods, wherein the thickness is 10 μm to 100 μm, the content of the inorganic electrolyte is ≥ 10%, preferably 15% to 50%. Furthermore, the mechanical strength is ≥ 4 MPa, and the ionic conductivity is 10 -6 S cm-1 ~10 - 1 S cm -1 With the good flexibility of the plasticizer and the spinning method, the 3D inorganic skeleton (also called the inorganic electrolyte 3D fiber skeleton) can be made extremely thin, which ensures that the thickness of the composite electrolyte membrane will not increase significantly after filling the polymer electrolyte, and the thickness can be controlled at 10μm to 100μm.

[0026] According to the third aspect of the present application, an all-solid-state energy storage device is also provided, which is assembled from an organic-inorganic composite ultra-thin solid electrolyte membrane and an electrode, and one or more layers of the above-mentioned inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane are arranged between the positive electrode and the negative electrode.

[0027] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0028] 1. In the present invention, inorganic electrolyte powder is prepared into long fibers with the aid of a plasticizer, and inorganic electrolyte particles are prepared into continuous fibers. The fibers are overlapped and stacked to form a skeleton, and the particles are evenly dispersed in the fibers and fixed by the fibers without agglomeration, thereby solving the problem of agglomeration of powder particles in the polymer matrix. In addition, there is force conduction between the fibrous inorganic particles, and a faster lithium ion transmission path is provided, which can improve the mechanical properties and ion conductivity of the organic-inorganic composite electrolyte membrane. Moreover, the fibers with inorganic electrolyte particles are overlapped and stacked with each other, thereby achieving a reinforced fiber structure, which helps to improve the mechanical strength of the composite electrolyte membrane.

[0029] The polymer electrolyte precursor is filled in the inorganic electrolyte 3D fiber skeleton, and the organic solvent is removed by heating to obtain the inorganic electrolyte 3D fiber self-supporting composite electrolyte membrane. Compared with the polymer electrolyte with low ion conductivity, the polymer electrolyte with 3D inorganic skeleton is added, and the powder particles are in close contact, which provides a faster ion transmission path, thereby improving the ion conductivity of the composite membrane. Compared with the direct filling of powder into the polymer matrix, in the present invention, the inorganic electrolyte is more evenly distributed, and the 3D fiber skeleton provides mechanical support, and the mechanical properties of the organic-inorganic composite membrane are greatly improved. The preparation process of the composite electrolyte membrane of the present invention has universality and can be widely used in the composite of various inorganic and organic electrolytes to improve their mechanical properties.

[0030] 2. In the present invention, with the shaping and fixing effect of the plasticizer, the inorganic particle powder is prepared into a uniformly distributed inorganic electrolyte 3D fiber skeleton by electrostatic spinning. The inorganic electrolyte 3D fiber skeleton itself is a porous mesh structure, and then filled with an organic polymer electrolyte precursor solution (i.e., a polymer electrolyte precursor solution) to prepare a 3D fiber self-supporting organic-inorganic composite ultra-thin solid electrolyte membrane. The electrolyte membrane is distributed with a uniform and continuous 3D porous skeleton, which improves the ionic conductivity and mechanical properties of the membrane, and can overcome the problems of uneven distribution of inorganic phases and poor mechanical properties of electrolytes in existing organic-inorganic composite electrolyte membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of the inorganic electrolyte 3D fiber skeleton prepared in Example 1 of the present invention, which has not yet been immersed in the polymer electrolyte precursor solution; the inorganic electrolyte powder is in close contact, providing a fast lithium ion transmission path, which is beneficial to the ionic conductivity and mechanical properties of the electrolyte membrane.

[0032] Figure 2 is a SEM image of the self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton in Example 1 of the present invention,

[0033] Figure 3 is a partial enlarged view of a photograph of a self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton in Example 1 of the present invention,

[0034] Figure 4 is a SEM image of the composite electrolyte membrane doped with inorganic electrolyte particles in Comparative Example 1. In Comparative Example 1, the inorganic electrolyte particles are directly added to the polymer electrolyte precursor solution without being fixed and dispersed by a plasticizer.

[0035] Figure 5 This is a partial enlarged view of the composite electrolyte membrane doped with inorganic electrolyte particles in Comparative Example 1.

[0036] Figure 6 is the thermogravimetric curve of the self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton in Example 1 of the present invention,

[0037] Figure 7 1 is the stress-strain curve of three electrolyte membranes of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. In Comparative Example 2, it is only an organic polymer electrolyte membrane prepared from a polymer electrolyte precursor solution without adding inorganic electrolyte particles.

[0038] Figure 8 It is the ionic conductivity test curve in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0040] The present invention provides a preparation method, product and application of an inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane. In engineering practice, it can adopt three practical steps to prepare an inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane:

[0041] S1: The inorganic electrolyte is prepared into fibers with the aid of a plasticizer, the aspect ratio of the fibers is ≥100, preferably ≥150, and the fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. S1 specifically comprises: dissolving the inorganic electrolyte and the plasticizer in a solvent, preparing a spinning solution, and using an electrospinning process or a wet spinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 5μm to 100μm. The inorganic electrolyte is an oxide solid electrolyte, including Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 0.33 La 0.557 TiO3、Li7La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 3.5 Si 0.5 P 0.5 The plasticizer is any one of or a combination of at least two of ethylene oxide (PEO), PEO-based polymer, polyvinylidene fluoride (PVDF), PVDF-based polymer, polyacrylonitrile (PAN), PAN-based polymer, polyethylene (PE) and polypropylene (PP). The solvent is volatile and can dissolve the plasticizer.

[0042] The viscosity of the spinning solution is configured to be 2-10 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 1:9:2 respectively, and the inorganic electrolyte is in a granular form with a particle size of D90≤2μm, preferably ≤200nm.

[0043] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB, and LiDFOB. The organic polymer molecule is any one of polyethylene oxide (PEO), PEO-based polymer, polyvinylidene fluoride (PVDF), PVDF-based polymer, polyacrylonitrile (PAN), and PAN-based polymer, or a combination of at least two of them. The viscosity of the polymer electrolyte precursor prepared by lithium salt, organic polymer molecules, and organic solvent is 3 to 12 Pa s.

[0044] There is no particular order for steps S1 and S2.

[0045] S3: Fill the polymer electrolyte precursor solution into the inorganic electrolyte 3D fiber skeleton, remove the organic solvent by vacuum heating, and obtain the inorganic electrolyte 3D fiber self-supporting composite electrolyte membrane. Fill the polymer electrolyte precursor solution into the inorganic electrolyte 3D fiber skeleton by scraping, immersion, spin coating or micro-negative pressure adsorption, and heat to remove the organic solvent.

[0046] In order to explain the method of the present invention in detail, it is further described below in conjunction with specific examples.

[0047] Example 1

[0048] S1: Dissolve the inorganic electrolyte and plasticizer in a solvent to prepare a spinning solution, and use the electrospinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fiber is 100. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 20μm.

[0049] In this embodiment, the inorganic electrolyte is an oxide solid electrolyte, which is Li 1.5 Al 0.5 Ge 1.5 (PO4)3. The plasticizer is ethylene oxide (PEO), and the solvent is volatile and can dissolve the plasticizer, which is acetonitrile.

[0050] In this embodiment, the viscosity of the spinning solution is set to 5 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 1:9:2 respectively, and the inorganic electrolyte is in granular form with a particle size of D90≤1.5 μm.

[0051] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is LiTFSI. The organic polymer molecule is polyethylene oxide (PEO). The mass ratio of lithium salt, organic polymer molecule and organic solvent is 5:3:60, and its viscosity is 5 Pa s.

[0052] There is no particular order for steps S1 and S2.

[0053] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by scraping, and the organic solvent is removed by vacuum heating at a temperature of 60°C for 24 hours.

[0054] In Example 1, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 25 μm, an inorganic electrolyte content of 18%, a mechanical strength of ≥4 MPa, and an ionic conductivity of 8.27×10 -4 S cm -1 .

[0055] Comparative Example 1

[0056] In comparative example 1, inorganic electrolyte particles are directly added to the polymer electrolyte precursor solution without being fixed and dispersed by a plasticizer. The preparation method comprises the following steps:

[0057] S1: Dissolve PEO powder and LITFSI salt in anhydrous acetonitrile. After they are fully dissolved, add LAGP powder (LAGP is the abbreviation of lithium aluminum germanium phosphate, a component of a solid electrolyte) and stir for 24 hours until the LAGP powder is evenly dispersed in the solution.

[0058] S2: The slurry is evenly coated on a polytetrafluoroethylene film by a scraping method. The prepared electrolyte membrane is dried at room temperature in a glove box for a period of time and then placed in a vacuum drying oven at 60° C. for 24 hours to remove residual solvent.

[0059] The contents and proportions of various substances in Comparative Example 1 are referenced to Example 1 and are compared with Example 1.

[0060] In Comparative Example 1, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 30 μm, an inorganic electrolyte content of 15%, a mechanical strength of 0.74 MPa, and an ionic conductivity of 3.33×10 - 4 S cm -1 .

[0061] Comparative Example 2

[0062] In Comparative Example 2, only the organic polymer electrolyte membrane prepared from the polymer electrolyte precursor solution is used, and no inorganic electrolyte particles are added. The preparation method is as follows: a certain amount of PEO powder and LITFSI salt are weighed and dissolved in anhydrous acetonitrile, and vigorously stirred under heating conditions until they are fully dissolved and mixed uniformly. The slurry is evenly scraped on the polytetrafluoroethylene film by a scraping method.

[0063] In Comparative Example 2, the thickness of the pure polymer electrolyte membrane prepared by the above method is 60 μm, its mechanical strength is 0.24 MPa, and its ionic conductivity is 2.40×10 -4 S cm -1 .

[0064] Figure 1 This is a SEM image of the inorganic electrolyte 3D fiber skeleton prepared in Example 1 of the present invention, which has not yet been immersed in the polymer electrolyte precursor solution. It can be seen from the figure that the inorganic electrolyte particles are evenly distributed and wrapped by the fibers, and the particles are in close contact with each other.

[0065] Figure 2 is a SEM image of the self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton in Example 1 of the present invention, Figure 3 It is a photograph of the self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton in Example 1 of the present invention and a partial enlarged view of the photograph. It can be seen from the figure that the inorganic particles in the electrolyte membrane prepared by this method are not agglomerated, but are closely connected, and can provide a fast lithium ion transmission path.

[0066] Figure 4 is a SEM image of the composite electrolyte membrane doped with inorganic electrolyte particles in Comparative Example 1, Figure 5 It is a photograph of the composite electrolyte membrane doped with inorganic electrolyte particles in Example 1 and a partial enlarged view of the photograph. In Example 1, the inorganic electrolyte particles are directly added to the polymer electrolyte precursor solution without being fixed and dispersed by a plasticizer. As can be seen from the figure, the inorganic particles are unevenly distributed and agglomerated. There is no mutual force between the particles, and lithium ion transmission is not easy to occur, resulting in poor mechanical properties and ionic conductivity of the electrolyte membrane.

[0067] Figure 6 This is the thermogravimetric curve of the self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton in Example 1 of the present invention. It can be seen from the figure that the content of inorganic electrolyte in the electrolyte membrane is 18wt%. The present method can greatly increase the content of inorganic powder in the composite electrolyte, and the inorganic powder is evenly distributed.

[0068] Figure 7It is the stress-strain curve of three electrolyte membranes of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, wherein PEO-LAGP Fiber refers to the sample of Example 1, PEO-LAGP Particle refers to the sample of Comparative Example 1, and PEO refers to the sample of Comparative Example 2. In Comparative Example 2, it is only an organic polymer electrolyte membrane prepared from a polymer electrolyte precursor solution, and no inorganic electrolyte particles are added. As can be seen from the figure, after being compounded with the inorganic filler LAGP, due to the interaction between the inorganic particles and the PEO molecules, the maximum tensile strength of the composite electrolyte in Comparative Example 1 is increased to 0.74MPa, but this is still not enough to be applied to actual battery assembly, and it is difficult to ensure that the all-solid-state battery operates stably during operation. The tensile strength of the fiber-reinforced composite electrolyte PEO-LAGP Fiber in Example 1 is 4.29MPa, which is nearly 18 times higher than the PEO electrolyte of Comparative Example 2 of the same thickness, and nearly 6 times higher than the tensile strength of the electrolyte in Comparative Example 1.

[0069] Figure 8 1 is the ionic conductivity test curve of Example 1, Comparative Example 1 and Comparative Example 2 of the present invention, wherein PEO-LAGP Fiber refers to the sample of Example 1, PEO-LAGP Particle refers to the sample of Comparative Example 1, and PEO refers to the sample of Comparative Example 2. It can be seen from the figure that the ionic conductivity of the electrolyte membrane in Example 1 is more significantly improved than that in Comparative Example 1 and Comparative Example 2. At a temperature of 60°C, the ionic conductivity of the electrolyte in Example 1 can reach 8.27×10 -4 S cm -1 , which is much higher than the ionic conductivity of PEO in Comparative Example 2 (2.40×10 -4 S cm -1 ), and also exceeded the electrolyte ion conductivity of Comparative Example 1 by nearly 2.5 times (3.33×10 -4 S cm -1 ).

[0070] Example 2

[0071] S1: Dissolve the inorganic electrolyte and plasticizer in a solvent to prepare a spinning solution, and use an electrospinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fiber is greater than 50. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 35μm.

[0072] In this embodiment, the inorganic electrolyte is an oxide solid electrolyte, including Li7La3Zr2O 12 and Li 6.4 LqCy 1.4 Ta0.6 O 12 A combination of two types. The plasticizer is a PEO-based polymer, and the solvent is volatile and can dissolve the plasticizer, and the solvent is acetonitrile.

[0073] In this embodiment, the viscosity of the spinning solution is set to 2 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 1:9:3 respectively, and the inorganic electrolyte is in a granular form with a particle size of D90≤1 μm.

[0074] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salts are LiBF4 and LiAsF6, and the mass ratio of LiBF4 and LiAsF6 is 7:3. The organic polymer molecules are polyvinylidene fluoride (PVDF). The optimal mass ratio of lithium salt, organic polymer molecules and organic solvent is 5:3:60, and its viscosity is 5 Pa s.

[0075] There is no particular order for steps S1 and S2.

[0076] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by scraping, and the organic solvent is removed by vacuum heating at a temperature of 60°C for 24 hours.

[0077] In Example 2, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 50 μm, an inorganic electrolyte content of 19%, a mechanical strength of 4.5 MPa, and an ionic conductivity of 7.6×10 - 4 S cm -1 .

[0078] Example 3

[0079] S1: Dissolve the inorganic electrolyte and plasticizer in a solvent to prepare a spinning solution, and use a wet spinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fibers is greater than 50. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 40μm.

[0080] In this embodiment, the inorganic electrolyte is an oxide solid electrolyte Li 1.5 Al 0.5 Ti 1.5 (PO4)3. The plasticizer is polyvinylidene fluoride. The solvent is volatile and can dissolve the plasticizer, and is N-methylpyrrolidone.

[0081] In this embodiment, the viscosity of the spinning solution is set to 10 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 3:9:2 respectively, and the inorganic electrolyte is in granular form with a particle size of D90≤0.5 μm.

[0082] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is a combination of LiPF6, LiClO4, LiBF4, and LiAsF6, and the mass ratio of LiPF6, LiClO4, LiBF4, and LiAsF6 is 3:3:3:1. The organic polymer molecules are a combination of PVDF-based polymers and polyacrylonitrile (PAN). The mass ratio of lithium salt, organic polymer molecules, and organic solvent is 5:3:60, and the viscosity is 5 Pa s.

[0083] There is no particular order for steps S1 and S2.

[0084] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by immersion, and the organic solvent is removed by vacuum heating at a temperature of 60°C for 24 hours.

[0085] In Example 3, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 50 μm, an inorganic electrolyte content of 22%, a mechanical strength of ≥5.2 MPa, and an ionic conductivity of 8.8×10 - 4 S cm -1 .

[0086] Example 4

[0087] S1: Dissolve the inorganic electrolyte and plasticizer in a solvent to prepare a spinning solution, and use an electrospinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fibers is greater than 50. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 60μm.

[0088] In this embodiment, the inorganic electrolyte is an oxide solid electrolyte, including Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3 and Li 3.5 Si 0.5 P 0.5O4. The plasticizer is a combination of ethylene oxide (PEO) and polyacrylonitrile (PAN). The solvent is volatile and can dissolve the plasticizer, and is a mixed solution of acetonitrile and N-methylpyrrolidone.

[0089] In this embodiment, the viscosity of the spinning solution is set to 2 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 1:9:3 respectively, and the inorganic electrolyte is in granular form with a particle size of D90≤0.8 μm.

[0090] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is a combination of equal masses of LiPF6, LiClO4, and LiBF4. The organic polymer molecule is polyvinylidene fluoride (PVDF). The mass ratio of lithium salt, organic polymer molecule and organic solvent is 6:3:60, and its viscosity is 8 Pa s.

[0091] There is no particular order for steps S1 and S2.

[0092] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by micro-negative pressure adsorption, and the organic solvent is removed by vacuum heating at a temperature of 60°C for 24 hours.

[0093] In Example 4, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 65 μm, an inorganic electrolyte content of 19%, a mechanical strength of ≥3.8 MPa, and an ionic conductivity of 9.3×10 -4 S cm -1 .

[0094] Example 5

[0095] S1: dissolving an inorganic electrolyte and a plasticizer in a solvent to prepare a spinning solution, and using a wet spinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fibers is greater than 80. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 80 μm.

[0096] In this embodiment, the inorganic electrolyte is an oxide and the solid electrolyte is Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 0.33 La 0.557 The combination of TiO3 and Li7La3Zr2O1, Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 0.33 La0.557 The mass ratio of TiO3 to Li7La3Zr2O1 is 3:3:4. The plasticizer is a combination of ethylene oxide (PEO), polyvinylidene fluoride (PVDF) and polyacrylonitrile (PAN). The solvent is volatile and can dissolve the plasticizer, and is acetonitrile.

[0097] In this embodiment, the viscosity of the spinning solution is set to 6 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 2:9:2 respectively, and the inorganic electrolyte is in granular form with a particle size of D90≤1 μm.

[0098] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is a combination of LiTFSI, LiFSI, LiBOB and LiDFOB. The organic polymer molecules are a combination of polyethylene oxide (PEO) and polyacrylonitrile (PAN). The mass ratio of lithium salt, organic polymer molecules and organic solvent is 5:3:65, and the viscosity is 4 Pa ​​s.

[0099] There is no particular order for steps S1 and S2.

[0100] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by spin coating adsorption method, and the organic solvent is removed by vacuum heating at a temperature of 60°C for 24 hours.

[0101] In Example 5, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 100 μm, an inorganic electrolyte content of 21%, a mechanical strength of ≥4.1 MPa, and an ionic conductivity of 8.0×10 -4 S cm -1 .

[0102] Example 6

[0103] S1: Dissolve an inorganic electrolyte and a plasticizer in a solvent to prepare a spinning solution, and use an electrospinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fibers is greater than 50. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 70 μm.

[0104] In this embodiment, the inorganic electrolyte is an oxide and the solid electrolyte is Li 1.5 Al 0.5 Ti 1.5 (PO4)3. The plasticizer is a combination of ethylene oxide (PEO) and a PEO-based polymer. The solvent is volatile and can dissolve the plasticizer, and is acetonitrile.

[0105] In this embodiment, the viscosity of the spinning solution is set to 9 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 4:9:2 respectively, and the inorganic electrolyte is in granular form with a particle size of D90≤1.5 μm.

[0106] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is LiPF6. The organic polymer molecules are a combination of polyacrylonitrile (PAN) and PAN-based polymer. The mass ratio of lithium salt, organic polymer molecules and organic solvent is 6:3:60, and its viscosity is 7 Pa s.

[0107] There is no particular order for steps S1 and S2.

[0108] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by immersion, and the organic solvent is removed by vacuum heating at a temperature of 70°C for 24 hours.

[0109] In Example 6, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 80 μm, an inorganic electrolyte content of 30%, a mechanical strength of ≥5 MPa, and an ionic conductivity of 9.2×10 -4 S cm -1 .

[0110] Example 7

[0111] S1: Dissolve the inorganic electrolyte and plasticizer in a solvent to prepare a spinning solution, and use a wet spinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton. The plasticizer coats the inorganic electrolyte and forms fibers. The aspect ratio of the fibers is greater than 60. The fibers are overlapped and stacked to form an inorganic electrolyte 3D fiber skeleton. The thickness of the inorganic electrolyte 3D fiber skeleton is 90 μm.

[0112] In this embodiment, the inorganic electrolyte is an oxide solid electrolyte, including Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 0.33 La 0.557 TiO3、Li7La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 3.5 Si 0.5 P 0.5The plasticizer is a combination of polyethylene (PE) and polypropylene (PP). The solvent is volatile and can dissolve the plasticizer, and is a 1,3-dioxolane mixed solvent.

[0113] In this embodiment, the viscosity of the spinning solution is set to 5 Pa s, wherein the mass ratios of the inorganic electrolyte, the plasticizer and the solvent in the spinning solution are 1:9:2 respectively, and the inorganic electrolyte is in granular form with a particle size of D90≤1 μm.

[0114] S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. The lithium salt is a mixed lithium salt of LiClO4, LiBF4, LiAsF6, LiBOB and LiDFOB. The organic polymer molecule is polyvinylidene fluoride (PVDF). The mass ratio of lithium salt, organic polymer molecule and organic solvent is 5:3:60, and its viscosity is 5 Pa s.

[0115] There is no particular order for steps S1 and S2.

[0116] S3: The polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by scraping, and the organic solvent is removed by vacuum heating at a temperature of 80°C for 24 hours.

[0117] In Example 7, the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane prepared by the above method has a thickness of 70 μm, an inorganic electrolyte content of 19%, a mechanical strength of ≥4.4 MPa, and an ionic conductivity of 8.2×10 -4 S cm -1 .

[0118] The inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane in Example 1 can be used in an all-solid-state energy storage device, which is assembled from an organic-inorganic composite ultra-thin solid electrolyte membrane and an electrode, and one or more layers of the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane as described above are arranged between the positive electrode and the negative electrode.

[0119] The present invention, with the help of the shaping and fixing effects of the plasticizer, pre-prepares the inorganic particle powder into a uniformly distributed inorganic electrolyte 3D fiber skeleton, and then fills the interior of the skeleton with an organic polymer electrolyte. This can overcome the difficulties of low inorganic phase content, easy agglomeration and difficulty in dispersion during the preparation of existing organic-inorganic composite electrolyte membranes, as well as the problems of insufficient ionic conductivity and poor mechanical properties of the composite electrolyte membrane.

[0120] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton, characterized in that: It includes the following steps: S1: Inorganic electrolyte powder is preformed into long fibers with the aid of a plasticizer, the aspect ratio of the fibers is ≥100, and the fibers are interlaced and overlapped to form an inorganic electrolyte 3D fiber skeleton. S2: Dissolve lithium salt and organic polymer molecules in an organic solvent to prepare a polymer electrolyte precursor solution. S3: Filling the polymer electrolyte precursor solution into the inorganic electrolyte 3D fiber skeleton, heating to remove the organic solvent, and obtaining the inorganic electrolyte 3D fiber skeleton self-supporting composite electrolyte membrane, There is no particular order for step S1 and step S2.

2. The method according to claim 1, characterized in that Step S1 is specifically as follows: dispersing inorganic electrolyte powder and plasticizer in a solvent to prepare a spinning solution, and using an electrospinning process or a wet spinning process to prepare the spinning solution into an inorganic electrolyte 3D fiber skeleton, wherein the mass content of the inorganic electrolyte phase in the long fiber is ≥50%, and the fiber diameter is ≥200nm.

3. The method according to claim 2, characterized in that Inorganic electrolytes are oxide solid electrolytes, including Li 1.5 Al 0.5 Ge 1.5 (PO4)3、Li 1.5 Al 0.5 Ti 1.5 (PO4)3、Li 0.33 La 0.557 TiO3、Li7La3Zr2O 12 , Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3、Li 3.5 Si 0.5 P 0.5 Any one or a combination of at least two of O4, The plasticizer is any one of ethylene oxide, ethylene oxide-based polymers, polyvinylidene fluoride, polyvinylidene fluoride-based polymers, polyacrylonitrile, polyacrylonitrile-based polymers, polyethylene and polypropylene, or a combination of at least two thereof. The solvent is volatile and can dissolve the plasticizer.

4. The method according to claim 2, characterized in that The thickness of the inorganic electrolyte 3D fiber skeleton is 5 μm to 100 μm, the viscosity of the spinning solution is configured to be 2 to 10 Pa s, and the inorganic electrolyte is in a granular form with a particle size of D90≤2 μm.

5. The method according to claim 2, characterized in that The lithium salt is one or more of LiPF6, LiClO4, LiBF4, LiAsF6, LiTFSI, LiFSI, LiBOB, and LiDFOB, The organic polymer molecule is any one of polyethylene oxide, polyethylene oxide-based polymer, polyvinylidene fluoride, polyvinylidene fluoride-based polymer, polyacrylonitrile and polyacrylonitrile-based polymer, or a combination of at least two thereof.

6. The method according to claim 2, characterized in that In step S2, the viscosity of the polymer electrolyte precursor solution is 3-12 Pa s.

7. The method according to claim 2, characterized in that In step S3, the polymer electrolyte precursor solution is filled into the inorganic electrolyte 3D fiber skeleton by scraping, immersing, spin coating or slight negative pressure adsorption, and the organic solvent is removed by heating to solidify into a film.

8. The self-supporting composite electrolyte membrane reinforced with an inorganic electrolyte 3D fiber skeleton prepared by the method according to any one of claims 1 to 7, characterized in that: The thickness is 10 μm to 100 μm, and the content of the inorganic electrolyte is ≥ 10%.

9. An all-solid-state energy storage device, assembled from an organic-inorganic composite ultra-thin solid electrolyte membrane and electrodes, characterized in that: One or more layers of the inorganic electrolyte 3D fiber skeleton reinforced self-supporting composite electrolyte membrane as claimed in claim 8 are arranged between the positive electrode and the negative electrode.

Citation Information

Patent Citations

  • Lithium ion battery interlayer solid-state electrolyte and a preparation method thereof

    CN109802171A

  • Oxide type ceramic composite nanofiber solid electrolyte and electrostatic spinning preparation method thereof

    CN111910283A

  • Preparation method and application of high-strength solid-state composite electrolyte film

    CN113161604A

  • Preparation method of composite negative electrode of lithium battery

    CN113809390A